Strategic Imperatives: A Rigorous Examination of Needs Analysis in ESP Law Education for Optimal Learning Outcomes - Rachmawati, Dwita Laksmita (Nexus Publishing, 2024)
There are 2 major categories in the field of English language teaching according to learning objectives and who the students are targeted for, namely General English and English for Specific Purposes (ESP). In ESP teaching, one of the pillars that plays a vital role is needs analysis as a basis for preparing or changing the curriculum. In the context of English learning at the Faculty of Law, research in the form of a needs analysis was carried out to find out whether the learning carried out was in accordance with the needs of the world of work (stakeholders) and the needs of the students. The results of this research become the basis for whether or not it is necessary to review and update the curricu lum or English for Law learning system at Unmer Pasuruan. The research was conducted with three informants: legal practition ers as representatives of the stakeholders, alumni of the Faculty of Law, and active students of the Faculty of Law. The instru ments used were semi-structured interviews and questionnaires. The results of interviews stated that the materials and methods for learning English for Law were in accordance with the faculty curriculum and the objectives of the study. Students experience an increase in their English language skills, both passively and ac tively. They also realize that mastering English for Law will be useful in their real life. Alumni, stakeholders, and practitioners suggest that there should be an added focus on learning speaking and writing, including through case analysis presentations in Eng lish. Keywords: Needs Analysis, stakeholders, student needs, English for Law